2016
DOI: 10.1016/j.anaerobe.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens type A netF and netE positive and Clostridium difficile co-infection in two adult dogs

Abstract: The aim of this study was to report two cases of Clostridium perfringens type A and Clostridium difficile co-infection in adult dogs. Both animals were positive for A/B toxin. Toxigenic C. difficile and C. perfringens type A positive for NetE and NetF-encoding genes were isolated. This report reinforces the necessity of studying a possible synergism of C. difficile and C. perfringens in enteric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…This sample was obtained from an adult dog, aged two years old. So far, C. perfringens netE þ strains were exclusively recovered from diarrheic adult dogs elsewhere [8,14], which corroborates our findings. In addition, the stool sample of this dog was positive for CPE in EIA.…”
Section: Perfringens In Cpv-positive Dogssupporting
confidence: 90%
See 1 more Smart Citation
“…This sample was obtained from an adult dog, aged two years old. So far, C. perfringens netE þ strains were exclusively recovered from diarrheic adult dogs elsewhere [8,14], which corroborates our findings. In addition, the stool sample of this dog was positive for CPE in EIA.…”
Section: Perfringens In Cpv-positive Dogssupporting
confidence: 90%
“…Thus, although these methods could suggest that C. perfringens is involved, they are not confirmatory [30]. Recently, studies have shown that two poreforming toxins (NetE, NetF) present in C. perfringens type A strains are strongly associated with canine hemorrhagic gastroenteritis [8,14], suggesting these toxin-encoding genes could be used as virulence markers to diagnose CPAD in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, toxigenic C. difficile and netF-positive C. perfringens were detected together in three animals ( Table 2). These are the first confirmed coinfections of these strains in dogs and two of these cases have been described in more details in a case report [26]. Among other enteropathogens, Giardia sp.…”
mentioning
confidence: 62%
“…Our results suggest that C. perfringens was the driver of enteritis in the DZ birds, while in the CZA birds, either C. colinum , or C. perfringens , or both acting synergistically, could have been driving the infections or creating a dysbiotic environment that allowed the other to thrive. Synergistic C. perfringens / C. colinum co-infections have been reported previously in poultry [ 78 ], while other clostridial co-infections ( C. perfringens / C. difficile ) have been reported in humans, foals, and dogs [ 79 81 ]. Phylogenetically related bacterial taxa can share functional traits and fill similar metabolic niches [ 82 ]; thus, it is feasible that an environment permissive to one type of clostridia may also be permissive to another clostridia.…”
Section: Discussionmentioning
confidence: 99%